1994
DOI: 10.3354/dao018165
|View full text |Cite
|
Sign up to set email alerts
|

Use of the polymerase chain reaction (PCR) to detect DNA from Renibacterium salmoninarum within individual salmonid eggs

Abstract: Renibacterium salmoninarum, the causative agent of bacterial kidney disease (BKD) in salrnonids, can be transmitted vertically, i.e. from parent to progeny via the egg. The usual procedure to determine the likelihood of egg infection has been to examine non-egg tissues from mature female fish for evidence of R. sahoninarum cells or antigens. In the present study we examined the feasibility of detecting the pathogen directly within individual salmonid eggs by use of the polymerase chain reaction (PCR) to amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 14 publications
1
65
0
Order By: Relevance
“…The polymerase chain reaction (PCR) was a variation of the protocol described by Brown et al (1994). Renibactedum salmoninarum was suspended to an ODGOOnm of 1.0 in sterile buffer (10 mM Tris-HC1, 1 mM sodium-EDTA, 0.35 M sucrose) and a 200 pl volume was incubated for 30 min at 25'C in the presence of 2% SDS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerase chain reaction (PCR) was a variation of the protocol described by Brown et al (1994). Renibactedum salmoninarum was suspended to an ODGOOnm of 1.0 in sterile buffer (10 mM Tris-HC1, 1 mM sodium-EDTA, 0.35 M sucrose) and a 200 pl volume was incubated for 30 min at 25'C in the presence of 2% SDS.…”
Section: Methodsmentioning
confidence: 99%
“…The primers Rsl and Rs2, which amplify a 501 basepair (bp) region of the gene encoding p57, were described by Brown et al (1994) and were synthesized by the Laboratory Services Division, University of Guelph. The PCR assay was conducted under the following conditions: 1 mM Tris-HC1,5 mM KC1,O.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, it was demonstrated that 16s rRNA gene primers can be used to detect as little as 1 pg to 10 fg of Photobacterium damselae purified DNA (Osorio et al 1999). Nevertheless, the sensitivity of the multiplex PCR should not be affected by the difference in gene copy numbers, since very good results and low detection levels are usually obtained for other fish pathogens when a single-copy gene is used as a target for PCR (Brown et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found even lower levels of vertical transmission (1 to 6%) (Evelyn et al 1986, Lee & Evelyn 1989. While a more recent study has suggested that 31 Dis Aquat Org 65: [29][30][31][32][33][34][35][36][37][38][39][40][41] 2005 these numbers might underestimate actual vertical infection rates due to incomplete detection (Brown et al 1994), vertical transmission alone, without evidence of increased horizontal transmission, immunosuppression, or both, is unlikely to account for large increases in infection or decreases in survivorship of progeny of infected females, especially if the majority of these spawners have only low to moderate infection levels, as was the case in the 1988 Dworshak brood stock segregation study.It may be that the p57 antigen in soluble form is taken up by eggs from the surrounding ovarian fluid or introduced directly from the bloodstream during oogenesis. Alternatively, vertical infection and subsequent antigen secretion could result in high antigen concentrations within the egg.…”
mentioning
confidence: 99%